2020
DOI: 10.1111/1753-0407.13053
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic properties of hydroxychloroquine in patients with diabetes: Risks and benefits at the time of COVID‐19 pandemic

Abstract: The antimalarial drug hydroxychloroquine (HCQ) has long been used as a disease-modifying antirheumatic drug for the treatment of several inflammatory rheumatic diseases. Over the last three decades, various studies have shown that HCQ plays also a role in the regulation of glucose homeostasis. Although the mechanisms of action underlying the glucose-lowering properties of HCQ are still not entirely clear, evidence suggests that this drug may exert multifaceted effects on glucose regulation, including improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 82 publications
0
24
0
1
Order By: Relevance
“…Antihypoglycemic property of hydroxychloroquine in patients with diabetes and the risk benefits at the time of COVID-19 pandemic is major subject of discussion. Emerging evidence with regards to the current pandemic scenario shows that following COVID-19 infection diabetic patients have a greater risk for adverse outcomes [52]. There are several review articles published which support the effect of hydroxychloroquine in the early infection stage of COVID-19 [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Antihypoglycemic property of hydroxychloroquine in patients with diabetes and the risk benefits at the time of COVID-19 pandemic is major subject of discussion. Emerging evidence with regards to the current pandemic scenario shows that following COVID-19 infection diabetic patients have a greater risk for adverse outcomes [52]. There are several review articles published which support the effect of hydroxychloroquine in the early infection stage of COVID-19 [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that hydroxychloroquine (HCQ) can be successfully used in patients with diabetes due to its hypoglycemic effect [ 72 , 91 ]. The mechanisms by which the drug affects glycemic control are still not entirely clear, however, it is suggested that it improves insulin sensitivity, increases insulin secretion, reduces hepatic insulin clearance, and reduces systemic inflammation [ 92 ]. This drug appeared to be effective in treating COVID-19 [ 72 , 91 ].…”
Section: Interactions Between the Development Of Covid-19 And Thementioning
confidence: 99%
“…Moreover, HCQ may influence the activity of the High mobility group box 1 protein (HMGB1) [ 38 ], which is a ubiquitous and highly conserved endogenous damage-associated molecular pattern (DAMP) molecule involved in the pathogenesis of several inflammatory conditions [ 39 , 40 ]. In light of these mechanisms of action, HCQ may theoretically exert an indirect antiviral activity by reducing the low-grade systemic inflammation, which is a common feature of several chronic diseases (e.g., obesity, type 2 diabetes, and metabolic syndrome) that are associated with an increased prevalence of SARS-CoV-2 infection and adversely affect the outcomes of patients with COVID-19 [ 41 , 42 ]. Intriguingly, relatively low rates of hospital PCR-confirmed COVID-19 cases have been reported in patients with SLE and inflammatory arthritis when compared to patients with systemic autoimmune or immune-mediated rheumatic diseases, despite an expected greater use of immunosuppressants and corticosteroids [ 43 ].…”
Section: Possible Mechanisms Of Action Of Chloroquine and Hcq Againstmentioning
confidence: 99%
“…Some of the most serious HCQ-related side effects include retinal toxicity [ 12 , 79 ], neuromyotoxicity [ 80 85 ] and cardiotoxic effects leading to potentially lethal heart rhythm disorders, such as prolonged QT interval and ventricular arrhythmias [ 12 , 86 88 ]. Besides excluding subjects with known hypersensitivity to HCQ or 4-aminoquinoline compounds, upcoming trials investigating the use of HCQ should also consider to exclude the enrollment of patients with underlying coexisting conditions that increase the risk of HCQ-related side effects, such as: i) patients with preexisting retinopathy/maculopathy or history or risk for macular edema [ 89 , 90 ]; ii) patients with preexisting cardiomyopathy, heart failure, ventricular hypertrophy, left ventricular dysfunction, coronary artery disease and/or heart rhythm disorders such as long QT syndrome [ 27 , 91 93 ]; iii) diabetic patients with macrovascular and/or microvascular complications [ 42 ]; iv) electrolyte abnormalities such as hypokalemia and hypomagnesemia [ 93 ]; v) family history of premature sudden cardiac death or cardiac ion channelopathies [ 91 93 ]; vi) patients with preexisting myopathy and/or neuropathy; vii) patients with glucose-6-phosphate dehydrogenase (G6PD) deficiency [ 94 , 95 ], although chloroquine- and HCQ-induced hemolysis in subjects with G6PD-deficiency has not been conclusively proven [ 96 ]; viii) patients using certain concomitant QT interval-prolonging medications such as azithromycin [ 22 , 91 93 ]. Thus, baseline and follow-up electrocardiography to evaluate for prolonged QT interval may be advisable prior to and following the initiation of HCQ, even in clinical trial settings.…”
Section: Expert Opinionmentioning
confidence: 99%